Extracellular Histones Bind Vascular Glycosaminoglycans and Inhibit the Anti-Inflammatory Function of Antithrombin - Biswas, Indranil; Panicker, Sumith R; Cai, Xiaofeng S; Giri, Hemant; Rezaie, Alireza R (Cellular physiology and biochemistry, 2021)
Binding of histones to molecular pattern recognition receptors on endothelial cells and leukocytes provokes proinflammatory responses and promotes activation of coagulation. Histones also bind therapeutic heparins, thereby neutralizing their anticoagulant functions. The aim of this study was to test the hypothesis that histones can interact with the antithrombin (AT)-binding vascular glycosaminoglycans (GAGs) to induce inflammation and inhibit the anti-inflammatory function of AT. METHODS: We evaluated the heparin-binding function of histones by an AT-dependent protease-inhibition assay. Furthermore, we treated endothelial cells with histones in the absence and presence of AT and monitored cellular phenotypes employing established signaling assays. RESULTS: Histones neutralized AT-dependent anticoagulant function of heparin in both purified protease-inhibition and plasma-based assays. Histones also disrupted endothelial cell barrier-permeability function by a GAG-dependent mechanism as evidenced by the GAG-antagonist, surfen, abrogating their disruptive effects. Further studies revealed histones and AT compete for overlapping binding-sites on GAGs, thus increasing concentrations of one protein abrogated effects of the other. Histones elicited proapoptotic effects by inducing nuclear localization of PKC-δ in endothelial cells and barrier-disruptive effects by destabilizing VE-cadherin, which were inhibited by AT, but not by a D-helix mutant of AT incapable of interacting with GAGs. Finally, histones induced release of Weibel-Palade body contents, VWF and angiopoietin-2, and promoted expression of cell adhesion molecules on endothelial cells, which were all downregulated by AT but not by D-helix mutant of AT. CONCLUSION: We conclude that histones and AT compete for overlapping binding sites on vascular GAGs to modulate coagulation and inflammation.